2022
DOI: 10.1111/nph.18520
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground herbivory can promote exotic plant invasion through intra‐ and interspecific aboveground–belowground interactions

Abstract: Summary Aboveground herbivores and soil biota profoundly affect plant invasions. However, how they interactively affect plant invasions through plant–soil feedbacks (PSFs) remains unclear. To explore how herbivory by the introduced beetle Agasicles hygrophila affects Alternanthera philoxeroides invasions in China, we integrated multiyear field surveys and a 2‐yr PSF experiment, in which we examined how herbivory affects PSFs on the performance of native and invasive plants and the introduced beetles. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Hu et al, (2023) conducted an experiment to investigate the latitudinal and longitudinal allelopathic patterns of A. philoxeroides in China, finding that the allelopathic effects increased with latitude and decreased with longitude, and were determined by soluble protein (SP), free amino acids (FAA), plant polyphenol (PP), phosphorus (P) and potassium (K) contents of leaf, suggesting potential control strategies for reducing the component contents in the plant tissues. Recently, Gao et al,(2023) proposed that aboveground herbivory can facilitate the invasion of A. philoxeroides via both intra-and interspecific aboveground-belowground interactions based on multiyear field surveys and a 2-years plant-soil feedbacks (PSF) experiment. However, the interaction between native plants and invasive plants was not given much attention.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al, (2023) conducted an experiment to investigate the latitudinal and longitudinal allelopathic patterns of A. philoxeroides in China, finding that the allelopathic effects increased with latitude and decreased with longitude, and were determined by soluble protein (SP), free amino acids (FAA), plant polyphenol (PP), phosphorus (P) and potassium (K) contents of leaf, suggesting potential control strategies for reducing the component contents in the plant tissues. Recently, Gao et al,(2023) proposed that aboveground herbivory can facilitate the invasion of A. philoxeroides via both intra-and interspecific aboveground-belowground interactions based on multiyear field surveys and a 2-years plant-soil feedbacks (PSF) experiment. However, the interaction between native plants and invasive plants was not given much attention.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the poorer performance of plants in conspecific‐conditioned soils than in heterospecific‐conditioned soils, for example, due to the accumulation of host‐specific below‐ground enemies, may promote species coexistence (Bever et al, 1997; Kandlikar et al, 2019). On the contrary, the poorer performance of plants in heterospecific‐conditioned soils than in conspecific‐conditioned soils, for example, due to spillover of generalist enemies and the presence of non‐compatible mutualists, may promote species dominance and alien plant invasions (Callaway et al, 2004; Gao et al, 2023). Differences in such plant responses to conspecific‐ and heterospecific‐conditioned soils may also depend on the phylogenetic distance between the examined plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Due to evolutionary novelty, some alien species develop distinct rhizosphere communities and, compared to native plants, are differently affected by soil biota. For instance, some alien species accumulate abundant soil‐borne enemies that asymmetrically suppress native, but not alien, plants (Callaway et al, 2004; Gao et al, 2023), or establish novel associations with resident soil mutualists (Callaway et al, 2011), likely promoting their invasion. In a meta‐analysis, Zhang et al (2019) found that alien plant species alter the biomass and abundance of resident soil biota (including bacteria, detritivores and microbivores) differently through rhizosphere and litter inputs.…”
Section: Introductionmentioning
confidence: 99%
“…An article published in this issue of New Phytologist by Gao et al . (2023; pp. 2347–2359) is unique because it meets all of these requirements.…”
mentioning
confidence: 99%
“…Undertaking this work demands additional and sustained funding for long-term, complex and resource-intensive studies at different ecological scales. An article published in this issue of New Phytologist by Gao et al (2023;pp. 2347-2359) is unique because it meets all of these requirements.…”
mentioning
confidence: 99%